A NEW SYNTHETIC THIO-CHALCONE INTENDED AS A LIGAND FOR POLYMETALLIC COORDINATION COMPOUNDS: STRUCTURAL, ELECTROCHEMICAL AND THEORETICAL STUDY. - Moreno, Yanko (Journal of the Chilean Chemical Society, 2021)
The new chalcone, 1-(PYRIDIN-2-YL)-3-(THIOPHEN-2-YL)PROPENONE, has been synthesized and its crystal and molecular structure determined. An electrochemical characterization of the molecule disclosed some reversible and irreversible processes in its cathodic/anodic reactions. A density functional study was carried out in order to calculate the frontier molecular orbitals and the diffusion coefficient, which showed very good agreement with the experimental data.